MULTI-CHANNEL MAGNETOCARDIOGRAPH: CONTROL AND SOFTWARE - Voytovych, Igor; Primin, Myhailo; Vasyliev, Valery; Sutkovyy, Pavlo; Budnyk, Mykola; Nedayvoda, Igor; Rusanov, Anatoly; Ryzhenko, Tetyana (International Journal of Computing, 2014)
Purpose of the work was to present algorithms and software developed for working with multi-channel magneto-cardiograph. Such software is intended for control of operation and computer processing of magnetocardiographic (MCG) data obtained from the human heart. Magnetocardiograph is controlled as “virtual device” from PC mouse/keyboard, so as manually from electronic unit and all that through the control microprocessors embedded into hardware units. Software processing is performed both in on-line mode during process of data acquisition and in off-line manner during post-processing. Software allows preliminary processing, reconstruction and analysis of magnetic maps, and also inverse problem solution. Package is intended both for scientific studying of the heart electric activity and studying of MCG informative indexes for clinical diagnostic of cardiology diseases. Above software is planned to use at Strazhesko Institute of Cardiology (Kyiv) within framework of project supported by Science and Technology Center in Ukraine (STCU).